Features of accounting in plant (Journal of Economic Research & Business Administration, 2016)
Accounting in agriculture, as in any other field, is a system that provides collection, registration and generalization of all the information about this property, enterprise obligations expressed in monetary terms. It provides continuous and comprehensive document all without exception, operations carried out in the sector. Agriculture as a sector of the economy, characterized by a number of features that are defined by the action of natural factors in the basis. The specificity of agricultural accounting lies primarily in the fact that the production process is associated with wildlife, land in living organisms – animals and plants acting as the objects of labor. A significant part of the production cycle is focused on the impact on living organisms – growing them to certain of conditions, the acquisition of the necessary human useful properties, qualities. Due to interruptions caused by natural climatic conditions, the production cycle is much longer is in agriculture than in other industries.
Keywords: agriculture; crop production; animal husbandry.